Use of NSAIDs and acetaminophen and risk of spontaneous intestinal perforations in premature infants: a systematic review and meta-analysis - Hudson, Jo-Anna B. J.; Shabbir, Wardha; Hayawi, Lamia M.; Chan, Monica Lik Man; Barrowman, Nicholas; Sikora, Lindsey; Ferretti, Emanuela (Frontiers in Pediatrics, 2024)
Background Acquired spontaneous intestinal perforation or SIP occurs most commonly in the extremely premature infant population. As the incidence is rising, understanding modifiable factors such as common medication exposures becomes important for individualizing care. Methods The primary outcome was SIP in premature infants with exposure to indomethacin, ibuprofen, or acetaminophen. The systematic review and meta-analysis were conducted following the Cochrane methodology and PRISMA guidelines. Results The point estimates of three RCTs showed an increase in the risk of SIP with indomethacin exposure compared to no medication, the pooled estimate was not statistically significant. There is no statistically significant association between the risk of SIP for indomethacin with treatment use over prophylactic use and when holding feeds. Ibuprofen conferred less risk than indomethacin, and its route of administration did not alter the risk profile. There was not enough evidence to draw conclusions about the risk of SIP and acetaminophen exposure. Conclusion In studies of infants exposed to either indomethacin or ibuprofen in the last 40 years, the incidence of SIP is still commonly within 2–8%. Moving forward modifiable factors such as medication exposure will help guide care to minimize risk where possible. Systematic Review Registration https://www.crd.york.ac.uk/, PROSPERO (CRD42017058603).